Rain water quality assessment as air quality indicator in Pakistan (Bangladesh Journal of Scientific and Industrial Research, 2019)
Rain is an effective way for removing pollutants from the atmosphere. The present study was initiated to determine rain water quality for its safe use as potable water, as well as a tool for indirect evaluation of air quality of different study areas. A total of 20 rain water samples were collected from areas including Kasur, Sheikhupura, Gujranwala and Lahore. The pH (5.49 + 0.323), turbidity (12.267 + 5.933NTU), Cl- (4785 + 1458.32ppm) and F- (16.44 + 4.52ppm) contents of samples are not in compliance with drinking water quality limits (Pakistan, WHO). Average sulphate (1.396 + 0.384 ppm) and NO3 − concentrations (52.35 + 12.11ppm) varied between 1.005-2.05ppm and 36.79-81.3ppm, respectively. Heavy metals analysis showed presence of Cu, Co, Mn and Zn concentrations below WHO limits while Cd and Pb concentrations exceeded WHO limits with values ranging between 0.005ppm-0.017ppm and 19ppm-254ppm, respectively . Findings indicate that rain water can provide an insight into the air quality of an area and its potential use as an alternative to drinking water, especially in areas of short domestic water supply.Bangladesh J. Sci. Ind. Res.54(2), 161-168, 2019